AB0273 Do patient-reported factors predict future orthopaedic operations in early rheumatoid arthritis? experience from the ERAN cohort. (23rd January 2014) - Mcwilliams, D.F.; Nikiphorou, E.; Varughese, S.; Young, A.; Kiely, P.; Walsh, D.A.
Abstract : Background: In rheumatoid arthritis (RA), orthopaedic surgery is an important outcome for patients and healthcare providers. We previously reported that disease activity predicted surgical intervention within 3 years of presentation with early RA [1]. Objectives: This study aimed to assess whether patient-reported measures of quality of life could predict surgical interventions in people with early RA after 5 years. Methods: The Early Rheumatoid Arthritis Network (ERAN) is an inception cohort of patients with early RA. Recruitment commenced in 2002, and still continues in the 22 centres in the UK and Eire. Data from annual study visits were cross-validated with the Hospital Episodes Statistics (HES) service, the National Joint Register (NJR) and National Death Register to provide longer follow up times. Factors associated with major joint replacement surgery or other orthopaedic operation 5 years after baseline were investigated. The SF36 subscales of vitality, mental health, bodily pain and physical function were used to estimate the patient experience. Data were analysed using logistic regression, and statistical significance was taken when p<0.05. Results: Using HES and NJR data 875 participants were followed up to 5 years. The cohort was 69% female, with a mean age of 56. Orthopaedic operations had been performed in 86 patients, including 35 total joint replacements, by 5 years. Sulfasalazine and methotrexate monotherapies were the commonest first choice treatments, and 9-10% of each had operations. Univariate analysis found that co-morbidity prevalence was higher and physical function was worse in those that had an orthopaedic operation. Logistic regression analysis found that physical function was associated with the risk of 5 year orthopaedic surgeries (Table 1). Previous smoking was also related to joint replacements. Conclusions: We were unable to confirm a link between baseline disease activity and subsequent orthopaedic surgery after 3 year follow up. High disease activity may damage joints, but may also delay surgery whilst the effects of more intense disease modifying therapy are evaluated. Poor physical function at baseline was the strongest independent predictor of orthopaedic surgery. We speculate that patients with high disability at baseline may have less scope for further functional deterioration, therefore seeking orthopaedic surgery whereas others may be more able to manage with conservative treatments. Further research would be required to determine whether more effective relief of disability in early RA would reduce or delay surgical episodes. References: Nikiphorou, E et al. Ann Rheum Dis. 2011;70(Suppl3). Disclosure of Interest: D. Mcwilliams Grant/Research support from: Pfizer Ltd, E. Nikiphorou: None Declared, S. Varughese: None Declared, A. Young: None Declared, P. Kiely: None Declared, D. Walsh Grant/Research support from: Pfizer Ltd, Consultant for: Pfizer Ltd